Expanding the impact of a longstanding Canadian cardiac registry through data linkage: challenges and opportunities. (2018) - Southern, Danielle A; James, Matthew T; Wilton, Stephen B; DeKoning, Lawrence; Quan, Hude; Kundtson, Merril L; Ghali, William A
No abstract available